Motif “homecoming” in the Story of Tatyana Gladkikh “Bird of God” - O. N. Alexandrova-Osokina (Научный диалог, 2020)
The story “The Bird of God” (2018), the work of the Far Eastern writer Tatyana Innokentyevna Gladkikh (born 1952), is reviewed in the article. The scientific novelty of the study is that the prose of Gladkikh was not a subject of comprehension in literary criticism. The relevance of this work is due to the importance of studying regional (Far Eastern) literature, which is a necessary condition for the formation of an integral picture of the domestic historical and literary process. The article presents the results of the immanent analysis of the story; attention is paid to issues of the plot, value content, figuratively motivational nature; the typology of the hero is traced and the typological parallel between the image of the hero of the story and the hero of medieval life - Alexy, the man of God, is justified. It is revealed that the hero of the story embodies the “hagiographic” type of world attitude, which manifests itself in a sense of universality with all living things, love, compassion. Particular attention is paid to the “homecoming” motive, which is seen as central in the plot-storyline and value-semantic organization of the work, and also acts as the organizing principle in the motive complex of the story, combining the images of “wandering”, “house”, “memory”, “soul”. The article traces how the “homecoming” motive is realized at three levels of organization of the artistic structure of the text: storyline, subjective and existential.